POTENSI ARANG AKTIF DARI TULANG KAMBING SEBAGAI ADSORBEN ION TEMBAGA, TIMBAL, NITRAT DAN SIANIDA DALAM LARUTAN - Ulul Azmi; Tengku Abu Hanifah; Sofia Anita (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
ne"> The utilization of animal bones as adsorbent has been widely studied. From several studies showed that animal bones has good potential as an adsorbent of heavy metals. However, the composition of the mineral constituent in bone of animals is different, and manufacturing process also affect the potential of bone as an adsorbent. In this study, the potential of goat bone activated charcoal as an adsorbent for Cu2+, Pb2+, NO3- and CNions have been studied. Activated charcoal of goat bones was made with the carbonization of goat bone at 700°C for 20 minutes, then crushed and sieved to obtain charcoal powder with a size of 100 – 120 mesh. The activation process performed using Na2CO3 activator with various concentration of 2.5%; 5% and 7.5% that contacted for 24 hours. The resulting of charcoal residue was dried and heated in a furnace at 800°C for 15 minutes, washed with distilled water and then dried. Activated charcoal that generated was characterized, and the best of activated charcoal according to the results of the characterization was used for adsorption of Cu2+, Pb2+, NO3- and CN- ions. From the results of characterization showed the goat bone activated charcoal which activated by Na2CO3 5% has the best result. The result of adsorption of Cu2+, Pb2+, NO3- and CN- ions showed that percentage of adsorption are 99,75%; 99,95%; 94,91% and 74,17% respectively. The highest of adsorption percentage of activated charcoal is Pb2+ ion and the lowest is CN- ion.